PLAY for LEARNING: Serious Games to Assist Learning of Basic Didactic Concepts: A Pilot Study - Rocha, Tânia; Barroso, João (HCI in Games: Serious and Immersive Games, 2021)
In this paper, the study of the design and implementation of a game-based application for learning new basic concepts and/or re-learning these concepts within a cognitive rehabilitation perspective, is presented. Specifically, in this first version, the topics considered were: colours, animals, objects, and vehicles. The solution was developed to be usable and accessible to two user groups, children with special education needs and seniors in need of cognitive training and/or rehabilitation. The two main goals are: (1) to develop a game-based interface for the two specific user groups – children with special educational needs and seniors; (2) and, assess user engagement and acceptance. To achieve the first goal a universal design methodology was followed. For the later, we performed a preliminary usability assessment. Specifically, a Cognitive Walkthrough reinforced with a post- test semi-structured interviews was conducted. Overall results showed a good user engagement and acceptance. The game-based solution seemed to facilitated children’ apprenticeship of basic contents and the helped in the cognitive rehabilitation by the seniors. The preliminary results indicated the solution could be used as an assistive tool, in a special education or in rehabilitation contexts, with tutors, teachers or clinicians; but also, in a more without obstruction and autonomous interaction, at home.